Natural Theology and a Priori Knowledge of God: A Lutheran Perspective on Gifford, Swinburne, and McGrath - Pandiangan, Tumpal; Sugiri, Widjaja (MAHABBAH: Journal of Religion and Education, 2024)
As the father of the Protestant Church reformer, Luther has made limitations on natural theology. He has criticized natural theology, even at first he rejected natural theology. However, today we see that natural theology has been constructed by several Protestant Christian theologians, among others: Gifford, Swinburne and Alister MacGrath. The problem is whether natural theology is in accordance with the doctrine or teachings of the Protestant Christian Church? The author's purpose is to find out whether the teachings of natural theology are in accordance with the doctrine of the Protestant Church and how they are applied in the life of the congregation? The research method was carried out with a literature study with the following stages: (i) First, observing and analyzing Luther's criticism of natural theology. (ii) Second, observing the limits of natural theology constructed by Gifford, Swinburne and Alister. (iii) Third, the author analyzes each of their definitions of natural theology. This analysis and evaluation is based on Luther's critique of natural theology. For Gifford's natural theology, knowledge of God is limited to a priori knowledge only, because knowledge is obtained from nature and the human mind not from God's revelation, whereas for Swimburne and McGrath, knowledge from nature stems from faith in Christ Jesus so that a priori knowledge of God can be known. For Swimburne, rational knowledge of nature can support faith in God, while McGrath does not require rationality in believing in God. In this case it is different from Luther, because according to him, the emergence of absolute faith is only by special revelation from God and nothing else, nor as a companion, so as not to become an idol.